Fine root dynamics of shaded cacao plantations in Costa Rica - Muñoz Arboleda, Fernando; Beer, JW (Springer, 2001)
Root turnover may contribute a significant proportion of recycled nutrients in agroforestry systems and competition between trees and crops for nutrients and water may depend on temporal fine root regrowth patterns. Fine root biomass (? 2 mm) and fine root productivity were measured during one year in plantations of cacao (Theobroma cacao) shaded by Erythrina poeppigiana or Cordia alliodora planted on a deep alluvial soil in Turrialba, Costa Rica. Fine root biomass of approximately 1.0 Mg ha?1 varied little during the year with maximum values at the beginning of the rainy season of 1.85 Mg ha?1 in the cacao-C. alliodora system compared to 1.20 Mg ha?1 for cacao-E. poeppigiana. Fine root productivity of C. alliodora and E. poeppigiana (maximum of 205 and 120 kg ha?1 4 week?1, respectively) was greatest at the end of the rainy season, while for cacao it was greatest at the beginning of the rainy season (34–68 kg ha?1 4 week?1), which suggests that if nutrient competition occurs between the shade trees and the cacao, it could be minimized by early fertilization during the beginning of the rains immediately after pruning the shade trees. Annual fine root turnover was close to 1.0 in both systems. Assuming that fine root biomass in these mature plantations was constant on an annual basis, nutrient inputs from fine root turnover were estimated as 23–24 (N), 2 (P), 14–16 (K), 7–11 (Ca) and 3–10 (Mg) kg ha?1 year?1, representing 6–13% and 3–6% of total nutrient input in organic matter in the C. alliodora and E. poeppigiana systems, respectively.